2015
DOI: 10.1038/srep09214
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and heritability of diurnal preference (chronotype) in a rural Brazilian family-based cohort, the Baependi study

Abstract: Diurnal preference (chronotype) is a useful instrument for studying circadian biology in humans. It harbours trait-like dimensions relating to circadian period and sleep homeostasis, but also has ontogenetic components (morningness increases with age). We used the Morningness-Eveningness questionnaire (MEQ) in the Baependi study, a family-based cohort study based in a small town in Minas Gerais, Brazil. The population is highly admixed and has a cohesive and conservative lifestyle. 825 individuals (497 female)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 48 publications
3
33
1
2
Order By: Relevance
“…For example, morning types reach their highest performance early during the day whereas evening types reach their peak performance in the afternoon, evening, or at night. M/E can be assessed by a set of questionnaires, and M/E is a heritable trait (von Schantz et al, 2015) with a genetic basis (Barclay, Watson, Buchwald, & Goldberg, 2014;Toomey, Panizzon, Kremen, Franz, & Lyons, 2015;Watson, Buchwald, & Harden, 2013). The variance in circadian preference is reflected in diurnal profiles of hormones, such as melatonin (Burgess & Fogg, 2008) or cortisol (Randler & Schaal, 2010) and body temperature (Baehr, Revelle, & Eastman, 2000;Mongrain, Lavoie, Selmaoui, Paquet, & Dumont, 2004).…”
Section: Morningness-eveningness (M/e)mentioning
confidence: 99%
“…For example, morning types reach their highest performance early during the day whereas evening types reach their peak performance in the afternoon, evening, or at night. M/E can be assessed by a set of questionnaires, and M/E is a heritable trait (von Schantz et al, 2015) with a genetic basis (Barclay, Watson, Buchwald, & Goldberg, 2014;Toomey, Panizzon, Kremen, Franz, & Lyons, 2015;Watson, Buchwald, & Harden, 2013). The variance in circadian preference is reflected in diurnal profiles of hormones, such as melatonin (Burgess & Fogg, 2008) or cortisol (Randler & Schaal, 2010) and body temperature (Baehr, Revelle, & Eastman, 2000;Mongrain, Lavoie, Selmaoui, Paquet, & Dumont, 2004).…”
Section: Morningness-eveningness (M/e)mentioning
confidence: 99%
“…CH is considered as the combination of both biological (genetic factors, aging of the body) and psychosocial (hours of study or work, the rhythm of family life) processes (Allebrandt and Roenneberg 2008). CH is highly heritable (heritability ~50%) (Koskenvuo et al 2007, von Schantz et al 2015. Studies suggested relationships between CH and both differences in the activation level (extraversion/ introversion, novelty seeking, mobility, strength of activation/inhibition of the nervous system) and severity of depression and anxiety (Frank et al 2013, Ottoni et al 2012.…”
Section: Objectivesmentioning
confidence: 99%
“…Most studies that have assessed the heritability of chronotype in populations have estimated it to be ~50%. [49][50][51] However, two studies have arrived at much lower estimates of 14% and 23%, 52,53 and notably chronotype was not normally distributed in these two populations. In the study of an Amazonian …”
Section: Does Athletic Activity Influence Chronotype?mentioning
confidence: 87%